Bambata Pottery and Western Bantu: re-interpreting the Early Iron Age in southern Africa - Huffman, Thomas N (Southern African Humanities, 2021)
New evidence indicates that Bambata pottery is part of the Kay Ladio Group centred in the Democratic Republic of Congo, rather than a facies of the Kalundu Tradition. This means that Western Bantu speakers produced the style. Other cornerstones of previous interpretations remain the same: Bambata derives from Benfica and it was spread to the southeast by hunter-gatherers. The distribution of Bambata also roughly marks the spread of Western Bantu-speaking people. In the Mount Buhwa area of Zimbabwe, Benfica people interacted with Eastern Bantu who produced Silver Leaves (Kwale), Ziwa/Gokomere (Nkope) and Happy Rest (Kalundu) pottery: thus, this was the confluence of four moving frontiers. These frontiers demonstrate the complexity of interaction, which in turn has linguistic ramifications.